Polycyclic aromatic hydrocarbons stress affects fatty acids profile and LacsA (long-chain acyl-CoA synthetize) gene expression in Dunaliella - Sajadinasab Jeyran; Siavash Hosseini; Manaffar Ramin; Pourakbar Latife (Applied Phycology)
This study was conducted to evaluate the effects of different concentrations of two Polycyclic Aromatic Hydrocarbons (PAHs) on the profiles of soluble proteins and fatty acids and on LacsA (long-chain acyl-CoA synthesis) gene expression in Dunaliella tertiolecta and Dunaliella salina. The algae were treated with a control and three experimental concentrations (3000, 6000 and 9000 μg l‒1) of phenanthrene and anthracene. In D. salina treated with 6000 and 9000 μg l‒1 of anthracene, expression of LacsA and α-linolenic acid was higher than in the control treatment. Also, at 3000 and 6000 μg l‒1 of anthracene, there was a sharp increase in hexadecenoic acid and docosahexaenoic acid (omega-3). Dunaliella tertiolecta treated with 9000 μg l‒1of anthracene showed a stronger protein expression profile than other samples which was consistent with LacsA gene expression at the same dose of anthracene. In D. tertiolecta, α-linolenic acid and 11-octadecenoic acid increased significantly at 9000 µg l‒1 of anthracene compared to the control, and there were similar trends in proteins, LacsA gene expression and α-linolenic acid and 11-octadecenoic fatty acids content. Phenanthrene and anthracene have different molecular structures, and it seems that they also have different dose-dependent effects on synthesis/accumulation of fatty acids, SDS-PAGE profiles of proteins and LacsA gene expression in D. salina and D. tertiolecta. According to previous reports, the LacsA gene is mediated by α-linolenic acid, hexadecenoic acid and docosahexaenoic acid (omega-3) synthesis. Since PAHs tend to be accumulated in the cell membrane of the microalgae, microalgae produce various proteins and fatty acids to bioremediate these harmful substances. Our results indicated that Dunaliella spp. may be good candidates for biodegradation purposes as well as an adequate model as a biotechnological accumulator of fatty acids under exposure to PAHs.